The role of mental and behavioral health in the application of the patient-centered medical home in the Department of Veterans Affairs - Kearney, Lisa K. (Springer-Verlag, 2011)
The patient-centered medical home, which is termed the Patient Aligned Care Team (PACT) in the Department of Veterans Affairs (VA), is a transformational initiative with mental and behavioral health as integral components. Funding has been provided to VA medical facilities to assist with the transformation and process redesign of primary care into interdisciplinary teams focused on increased access, Veteran-centered care, and active incorporation of collaborative expertise from specialists within primary care. Primary care clinics are not simple machines that change by merely replacing parts or colocating additional resources. Rather, they are complex systems with a relationship infrastructure among members of the team that is critically important to the change process. Mental health professionals are integral, mandated members of the PACTs providing needed mental and behavioral health care to Veterans as an integrated component of primary care. They also work to catalyze a quality improvement process that encourages collaboration, innovation, and adoption of best practices that promote transformation based on patient-centered principles of care. The purpose of this article is to describe the evolution of VA primary care settings toward interdisciplinary teams that provide patient-centered care in collaboration with Primary Care–Mental Health Integration providers and Health Promotion Disease Prevention team members.